2006
DOI: 10.1509/jmkr.43.4.654
|View full text |Cite
|
Sign up to set email alerts
|

Fading Optimism in Products: Temporal Changes in Expectations about Performance

Abstract: for their feedback on this project. This article has also benefited from the suggestions of Om Narasimhan, Rajesh Chandy, and the anonymous JMR reviewers. ASHWANI MONGA and MICHAEL J. HOUSTON*The authors demonstrate that choosing one product from a set of competing alternatives can change expectations about the chosen product such that consumers can become optimistic about the product's performance, and this optimism can then fade away. In five experiments, the authors show that this phenomenon of fading optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
(41 reference statements)
2
17
1
4
Order By: Relevance
“…In fact, recognizing the benefits of dechnes in expectations has critical imphcations for how people prepare themselves for potential bad news and how they respond if bad news comes. Emotional responses to feedback depend in large part on a comparison between expectations and outcomes (Meilers, Schwartz, Ho, & Ritov, 1997;Zeelenberg, van Dijk, Manstead, & van der Pligt, 2000), and people can (and do) capitalize on this psychological phenomenon by lowering their expectations in the face of feedback (Armor et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recognizing the benefits of dechnes in expectations has critical imphcations for how people prepare themselves for potential bad news and how they respond if bad news comes. Emotional responses to feedback depend in large part on a comparison between expectations and outcomes (Meilers, Schwartz, Ho, & Ritov, 1997;Zeelenberg, van Dijk, Manstead, & van der Pligt, 2000), and people can (and do) capitalize on this psychological phenomenon by lowering their expectations in the face of feedback (Armor et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, research suggests that, faced with uncertainty, certain types of consumers (e.g., satisficers, Schwartz et al 2002;perfectionists, Kopalle and Lehman 2001) may be motivated to prepare for the worst by lowering one's target level of achievement. Recent research on temporally shifting expectations has also shown that people lower their expectations downward as uncertainty and the possibility of a negative outcome loom larger (Monga and Houston 2006;van Dijk, Zeelenberg, and van der Pligt 2003). The tendency to set low goals is likely to be exacerbated when consumers are concerned about minimizing the negative affect that accompanies failure (van Dijk et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As time since purchase increases, consumers partially forget their pre-purchase expectations (Monga and Houston 2006) and the role of rational processes may thus diminish. Emotional processes may not suffer from this effect because they do not require standards of comparison (Pham 2004;Verplanken, Hofstee, and Janssen 1998).…”
Section: H3mentioning
confidence: 99%